Exploring the Embodiment of a Virtual Hand in a Spatially Augmented Respiratory Biofeedback Setting - Barresi, Giacinto; Marinelli, Andrea; Caserta, Giulia; de Zambotti, Massimiliano; Tessadori, Jacopo; Angioletti, Laura; Boccardo, Nicolò; Freddolini, Marco; Mazzanti, Dario; Deshpande, Nikhil; Frigo, Carlo Albino; Balconi, Michela; et al. (Frontiers in Neurorobotics, 2021)
Enhancing the embodiment of artificial limbs – the individuals’ feeling that a virtual or robotic limb is integrated in their own body scheme – is an impactful strategy for improving the users' acceptance and experience of such technological extensions and, consequently, the performance of human-machine systems. Most studies so far focused on visuo-tactile strategies to empower the embodiment processes. However, novel approaches could emerge from self-regulation techniques – like slow paced breathing – able to change the psychophysiological conditions of an individual. Accordingly, this pilot study investigates the effects of a self-regulated breathing exercise on the processes of body ownership underlying the embodiment of a virtual right hand within a Spatially Augmented Respiratory Biofeedback (SARB) setting with game-based features. This investigation also aims at evaluating the feasibility of the breathing exercise enabled by a SARB implementation based on a low-cost setup for upcoming remote studies (avoiding the restrictions caused by the COVID-19 pandemic). Twenty-two subjects without impairments, and two transradial prosthesis users for a preliminary test, were asked (in each condition of a within-group experimental design) to maintain a normal (about 14 breaths/minute) or slow (about 6 breaths/minute) respiratory rate to keep a static virtual right hand "visible" on a screen. Meanwhile, a computer-generated sphere moved from left to right towards the virtual hand during each trial (1 minute) of 16. If the participant’s breathing rate was within the target (slow or normal) range, a visuo-tactile event was triggered by the sphere passing under the virtual hand (the subjects observed it shaking while their right hand was simultaneously stimulated by a vibratory haptic feedback generated by a smartphone). Our preliminary data – mainly based on body ownership questionnaire scores and proprioceptive drift measures (collected after each session) – highlights that the slow breathing condition induced higher embodiment than the normal one. This preliminary study reveals the feasibility and potential of a novel psychophysiological training strategy to enhance the embodiment of artificial limbs in domains from telerehabilitation to prosthetics. Future studies are needed to further investigate mechanisms, efficacy and generalizability of the SARB setting in training a bionic limb embodiment.